LINGUISTIC ANALYSIS OF THE ECONOMIC IMPACT OF ADVERTISING TEXTS IN THE UZBEKISTAN LANGUAGE - Yuldasheva Dilnoza Bekmurodovna; Valiyev Asadbek Alisherovich (Web of Journals Publishing, 2025)
In this article, we conducted a linguistic analysis of advertising texts in the economic life of Uzbekistan. In the article, we studied the economic aspects of the language of advertising, analyzing what economic goals advertising texts serve in terms of language and meaning, and what linguistic techniques are used to advertise goods or services, and expressed our scientific views on this matter.
Keywords: Advertising texts, economic impact, linguistic analysis, economic consciousness, Uzbek language, features of the language of advertising, economic communication, language and economics, economic consciousness.